Management of Working Capital for an Enterprise - Mittal, Neeraj; Chauhan, S. S (Journal of Commerce and Trade, 2009)
Management of these short term assets and liabilities warrants a careful investigation, since the working capital management plays an important role in a firm’s profitability and risk as well as its value (smith, 1980). This paper firstly defines the concept, purpose, scope, types / kinds and components of Working Capital Management (WCM). Secondly, it analyzes that Working Capital Management (WCM) should not be excessive and inadequate as both are harmful to the business. Excessive and inadequate Working Capital Management (WCM) is dangerous for the components as well. So, we can say that working capital of an enterprise should be optimal.